2015
DOI: 10.1111/bju.12844
|View full text |Cite
|
Sign up to set email alerts
|

The role of functional polymorphisms in immune response genes as biomarkers of bacille Calmette-Guérin (BCG) immunotherapy outcome in bladder cancer: establishment of a predictive profile in a Southern Europe population

Abstract: Objective To evaluate the predictive value of genetic polymorphisms in the context of bacille Calmette‐Guérin (BCG) immunotherapy outcome and create a predictive profile that may allow discrimination of the risk of recurrence. Patients and Methods In a dataset of 204 patients treated with BCG, we evaluated 42 genetic polymorphisms in 38 genes involved in the BCG mechanism of action, using Sequenom MassARRAY® technology. Stepwise multivariate Cox regression was used for data mining. Results In agreement with pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 41 publications
0
25
0
3
Order By: Relevance
“…The results of the rechallenge test showed that antitumor immunity had been enhanced in the RF/BCG group, but could not suggest the benefits of adding BCG to RF ablation, and the mechanism of immunity enhanced by BCG still needs to be clarified. The strength of immune response is different between rabbit and man, and immunity based on genetic polymorphism is different in each individual (21). However, a combination of RF ablation and local injection of BCG may be capable of activating antitumor immunity, given that previous studies have reported that RF ablation activates antitumor immunity and that BCG is used as an immunostimulant in tumors in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the rechallenge test showed that antitumor immunity had been enhanced in the RF/BCG group, but could not suggest the benefits of adding BCG to RF ablation, and the mechanism of immunity enhanced by BCG still needs to be clarified. The strength of immune response is different between rabbit and man, and immunity based on genetic polymorphism is different in each individual (21). However, a combination of RF ablation and local injection of BCG may be capable of activating antitumor immunity, given that previous studies have reported that RF ablation activates antitumor immunity and that BCG is used as an immunostimulant in tumors in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…However, another study indicated that SNP-174(C/C) at IL-6 was associated with a decreased risk of recurrence (HR = 0.298) and an increased recurrence-free survival (RFS) [14]. Studies on TNF-a polymorphisms reported that the SNP rs1799964(C/C) at TNF-a was associated with a decreased risk of recurrence [6, 15]. Ahirwar et al found that rs4073 (at IL-8 ) was significantly associated with a decreased risk of recurrence ( p < 0.001) and an increased RFS ( p < 0.001) in patients who underwent BCG treatment after TURBT, but these results have not yet been confirmed [13].…”
Section: Evidence Synthesismentioning
confidence: 99%
“…First, genetic alterations in single nucleotides in numerous pathways were found to be closely associated with BCG response. These alterations included single-nucleotide polymorphisms (SNPs), single-nucleotide variations (SNVs), and mutations [5, 6]. Second, various genetic copy number alterations were associated with bladder cancer [7].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, efforts should continue to be devoted towards a more comprehensive and integrated understanding of bladder cancer pathways, the tumor microenvironment and cancer-associated immune responses and their influence in treatment response. Namely, future it would be important to ponder possible factors modulating targetmolecules expression and response profile to immunotherapy, such as the highly variable mutational spectrum of bladder cancers [19,180] and inter-patients variability, as translated by our most recent works in the field of pharmacogenetics [181][182][183]. The tumor microenvironment, in particular the immune responses occurring in stroma [184], is another critical aspect that as remained mostly disregarded and warrants careful investigation in the future.…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%